La agricultura nahua en el siglo XVI - González Jácome, Alba (CIENCIA ergo-sum; Vol. 8 Núm. 1 (2001): CIENCIA ergo-sum (marzo-junio 2001), 2015)
Alonso de Molinas Vocabulary is the main historical source followed by the author of this article in order to understand the Nahua agriculture at the end of the XVI century. There are also other historical sources utilized by Alba González to compare the information about types of soils, climate, vegetation, agricultural techniques and the technology associated with it and about irrigation. The article has broad information about agricultural managements and the uses of plants -mainly corn- utilized in the agricultural labor, which was basic in the life of the Nahuas in Central Mexico. It has several tables with the data obtained from the historical sources which permit to understand the richness of this economic activity. This article is important for agricultural, ecological and historical studies and the information it presents is valuable.